Tinjauan Maslahah Mursalah terhadap Tradisi Adat Manjapuik Sumando Setelah Kematian Istri di Nagari Koto Gadang Kecamatan Baso - Trisgia Trisgia; Dahyul Daipon (Lembaga Yasin AlSys, 2026)
The customary tradition of manjapuik sumando after the death of a wife in Minangkabau society has received attention in various studies, yet research that specifically analyzes this tradition from the perspective of maslahah mursalah remains limited. This study aims to explore the implementation of the customary tradition of manjapuik sumando after the death of a wife in Nagari Koto Gadang, Baso Subdistrict, Agam Regency, and to analyze its relevance from the perspective of maslahah mursalah. This study used a qualitative approach with a field research and case study design. The research informants included customary leaders, niniak mamak, bundo kanduang, Islamic religious scholars, nagari officials, and community members selected through purposive sampling and snowball sampling techniques. Data were collected through interviews, Focus Group Discussions (FGDs), observation, and documentation, and were then analyzed using the Miles, Huberman, and Saldaña model through the stages of data reduction, data display, and conclusion drawing. The results show that the tradition of manjapuik sumando is still maintained as a form of respect for the sumando, a mechanism for preserving kinship relations, and a means of maintaining social harmony in Minangkabau customary society. This tradition is viewed as bringing social benefit and not conflicting with the basic principles of Islamic law, so it can be understood as a form of ‘urf shahih. This study contributes to the development of Islamic legal studies, particularly regarding the relationship between custom and Islamic law in Minangkabau matrilineal society. The implications of this study include theoretical contributions to the development of maslahah mursalah studies and practical implications for customary leaders, Islamic religious scholars, and nagari governments in maintaining harmony between the preservation of local culture and Islamic values.